Characterization of acidosis in trauma patient - Gregory S Corwin; Kevin W Sexton; William C Beck; John R Taylor; Avi Bhavaraju; Benjamin Davis; Mary K Kimbrough; Joseph C Jensen; Anna Privratsky; Rotnald D Robertson (Journal of Emergencies, Trauma and Shock, 2020)
Background: Recent data suggest that acidosis alone is not a good predictor of mortality in trauma patients. Little data are currently available regarding factors associated with survival in trauma patients presenting with acidosis. Aims: The aims were to characterize the outcomes of trauma patients presenting with acidosis and to identify modifiable risk factors associated with mortality in these patients. Settings and Design: This is a retrospective observational study of University of Arkansas for Medical Sciences (UAMS) trauma patients between November 23, 2013, and May 21, 2017. Methods: Data were collected from the UAMS trauma registry. The primary outcome was hospital mortality. Analyses were performed using t-test and Pearson's Chi-squared test. Simple and multiple logistic regressions were performed to determine crude and adjusted odds ratios. Results: There were 532 patients identified and 64.7% were acidotic (pH < 7.35) on presentation: 75.9% pH 7.2–7.35; 18.5% pH 7.0–7.2; and 5.6% pH ≤ 7.0. The total hospital mortality was 23.7%. Nonsurvivors were older and more acidotic, with a base deficit >−8, Glasgow Coma Scale (GCS) ≤ 8, systolic blood pressure ≤ 90, International Normalized Ratio (INR) >1.6, and Injury Severity Score (ISS) >15. Mortality was significantly higher with a pH ≤ 7.2 but mortality with a pH 7.2–7.35 was comparable to pH > 7.35. In the adjusted model, pH ≤ 7.0, pH 7.0–7.2, INR > 1.6, GCS ≤ 8, and ISS > 15 were associated with increased mortality. For patients with a pH ≤ 7.2, only INR was associated with increase in mortality. Conclusions: A pH ≤ 7.2 is associated with increased mortality. For patients in this range, only the presence of coagulopathy is associated with increased mortality. A pH > 7.2 may be an appropriate treatment goal for acidosis. Further work is needed to identify and target potentially modifiable factors in patients with acidosis such as coagulopathy.